2015
DOI: 10.17507/tpls.0507.22
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teachers’ Storytelling and Reading Story Aloud on the Listening Comprehension of Iranian EFL Learners

Abstract: Abstract-This study was an attempt to compare the effect of reading story aloud (RSA) and storytelling (ST) on intermediate EFL learners' listening comprehension. The design of the study was quasi experimental with listening pre and post tests. The participants were 99 Iranian EFL learners who were selected based on their performance on a Placement and Evaluation Package. For 6 sessions, the participants of both experimental groups who were 66 students listened to their teacher reading a story aloud in group 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Comparative study on the effect of reading story aloud and storytelling on intermediate EFL learners' listening comprehension was conducted by Hemmati, Gholamrezapour & Hessamy (2015) their findings indicate that that both Storytelling and story reading aloud groups had positive effects on the students' listening comprehension. However, the exact comparison of these two groups shows Storytelling group better performed than story reading group in posttests.…”
Section: Research On Effects Of Storytelling and Story Readingmentioning
confidence: 99%
“…Comparative study on the effect of reading story aloud and storytelling on intermediate EFL learners' listening comprehension was conducted by Hemmati, Gholamrezapour & Hessamy (2015) their findings indicate that that both Storytelling and story reading aloud groups had positive effects on the students' listening comprehension. However, the exact comparison of these two groups shows Storytelling group better performed than story reading group in posttests.…”
Section: Research On Effects Of Storytelling and Story Readingmentioning
confidence: 99%
“…The aspects of vocabulary include word meaning (i.e., synonym, antonym, connotation, and denotation), extending word use such as idioms, word combination, or collocation, and grammar, verbs, adjectives, and adverbs (Harmer, 2001). Experts have argued that these aspects of vocabulary are positively impacted through reading aloud among children because the teacher's clear speaking style during reading aloud can substantially impact the students' sentence recognition memory, through which the students can recall their prior vocabularies or gain new words (Batini et al, 2018;Bullinaria, 2014;Cerón, 2014;Draper, 1993;Giroir et al, 2015;Hemmati, Gholamrezapour, & Hessamy, 2015;G. Jacobs & Hannah, 2004;Johnston, 2015;Kindle, 2009;Novianti & Abdurahman, 2019;Proença et al, 2017;Trelease, 1989;Yusuf, Yusuf, Yusuf, & Nadya, 2017).…”
Section: Reading Aloud For Improving English Vocabularymentioning
confidence: 99%
“…For Huang (2010), the pauses in reading aloud give moments for the students to let the information they hear sink into their minds. This process is important because this is where the students make connections among bits of information that they hear and between the new information with their repertoire prior knowledge, creating an understanding that becomes the basis of their comprehension (Draper, 1993;Hahn, 2002;Hemmati et al, 2015;Jacobs & Renandya, 2019;Kailani, 1998). According to Tarim (2015), Gurdon (2019), Johnston (2015), Lane & Wright (2007), Novianti &Abdurahman (2019), andTrelease (1989), the simple questions asked by the teacher during reading aloud activity cultivate the students' comprehension by guiding them through the process of connecting information from the story and the information from the students' life in general.…”
Section: Reading Aloud For Cultivating Comprehensionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies have been conducted to find out the effectiveness of the application of storytelling in teaching listening comprehension. The results of the study showed that it is effective to improve the student listening comprehension (e.gHemmati, Gholamrezapour, &Hessamy, 2015), improve the student interest and motivation (e.gSandaran& Kia,2013) and could make the learning process to be more effective (Rasul, Bukhsh,&Batool, 2011). All those studies applied popular stories, fairy tale or legend.…”
Section: Introductionmentioning
confidence: 99%